Penggunaan Lethal Ovitrap Dengan Berbagai Jenis Attractant Untuk Pengendalian Nyamuk Aedes Sp - Aries Prasetyo; Sri Poerwati; Moch. Yulianto (Poltekkes Kemenkes Surabaya, 2016)
Background: Dengue fever, up to now been a problem for public health, as well as causing social impact, in terms of the number of people year after year tend to increase and expand the endemic area. One of the Aedes sp control methods is the use of lethal ovitrapObjective : To analyze the effectiveness (larvae of Aedes sp caught ) the use of lethal ovitrap with various types of attractant to control Aedes sp .Method : this study involves the quasi experiment and post test only control group design. Subject of the study is Aedes sp in nature. Data are analyzed descriptively and analytically by using One Way Anova statistical methods.Result discussion : The number of trapped- larvae of Aedes sp by lethal ovitrap without attractant between 13-15. the number of trapped larvae Aedes sp by lethal ovitrap with various attractant average ranges between 30-95 in door and the average range 9 – 44 out door. There are significant differences amount Aedes sp larvae were caught between treatment both indoor and outdoor ( p = 0.008 and p = 0.007 )Conclusion : There are significant differences amount Aedes larvae were caught between treatment both indoor and outdoor, and lethal ovitrap with shrimp shells attractant water immersion is the most effective way to control Aedes sp mosquitoesKeywords: Lethal Ovitrap, Aedes sp, attractant